Unbroken B-L symmetry - Heeck, Julian (Physics letters, 2014)
The difference between baryon number B and lepton number L is the only anomaly-free global symmetry of the Standard Model, easily promoted to a local symmetry by introducing three right-handed neutrinos, which automatically make neutrinos massive. The non-observation of any (B-L)-violating processes leads us to scrutinize the case of unbroken gauged B-L; besides Dirac neutrinos, the model contains only three parameters, the gauge coupling strength g′, the Stückelberg mass MZ′, and the kinetic mixing angle χ. The new force could manifest itself at any scale, and we collect and derive bounds on g′ over the entire testable range MZ′=0-1013 eV, also of interest for the more popular case of spontaneously broken B-L or other new light forces. We show in particular that successful Big Bang nucleosynthesis provides strong bounds for masses 10 eV<MZ′<10 GeV due to resonant enhancement of the rate f¯f↔ν¯RνR. The strongest limits typically arise from astrophysics and colliders, probing scales MZ′/g′ from TeV up to 1010 GeV.
Gesehen am 20.10.2020